Impact of Gallic Acid on Gut Health: Focus on the Gut Microbiome, Immune Response, and Mechanisms of Action - Yang, Kang; Zhang, Limeng; Liao, Pinfeng; Xiao, Zaili; Zhang, Fan; Sindaye, Daniel; Xin, Zhongquan; Tan, Chengquan; Deng, Jinping; Yin, Yulong; Deng, Baichuan (Frontiers in Immunology, 2020)
Gallic acid (GA) is a naturally occurring polyphenol compound present in fruits, vegetables, and herbal medicines. According to previous studies, GA has many biological properties, including antioxidant, anticancer, anti-inflammatory, and antimicrobial properties. GA and its derivatives have multiple industrial uses, such as food supplements or additives. Additionally, recent studies have shown that GA and its derivatives not only enhance gut microbiome (GM) activities, but also modulate immune responses. Thus, GA has great potential to facilitate natural defense against microbial infections and modulate the immune response. However, the exact mechanisms of GA acts on the GM and immune system remain unclear. In this review, first the physicochemical properties, bioavailability, absorption, and metabolism of GA are introduced, and then we summarize recent findings concerning its roles in gastrointestinal health. Furthermore, the present review attempts to explain how GA influences the GM and modulates the immune response to maintain intestinal health.